INFECTIONS AND FOLLICULAR LYMPHOMA: IS THERE A LINK? - Francesco Zallio; Giulia Limberti; Marco Ladetto (Mediterranean Journal of Hematology and Infectious Diseases)
Several infectious agents appear to provide a proliferative signal -- “antigen-drive” – that  could be implicated in the pathogenesis of various type of Non-Hodgkin Lymphoma (NHL). A classical model of infection-driven lymphoprolipherative disorder is Helicobacter pylori-induced gastric MALT lymphoma, where antibiotic therapy allows eradication of both the infectious agent and the clonal B-cell expansion;  following the footsteps of these example, several retrospective studies have found a correlation with other pathogens and B-cell Lymphomas, adding new important informations about pathogenesis and laying the groundwork for chemotherapy-free treatments.